Psycho-sociological variables predicting cultic behaviour among undergraduates in South-West, Nigeria (2018)
The incidence of cultic behaviour such as murder violence is becoming increasing in Nigerian tertiary institutions. The menace of this behaviour remains indelible in the minds of the victims and members of the society at large. In fact it has posed serious problems to parents, guardians, educators and management of tertiary institutions at large. This study therefore investigated psycho-sociological variables in predicting cultic behaviour among undergraduates in South-West Nigeria. The descriptive research design of the correlational type was adopted. The sample consisted of 1,200 participants from three federal and three State Universities. Data was collected and analysed using Multiple Regression and Pearson Product Moment Correlation. The results showed that there was a positive and significant relationship between self-efficacy, aggression, drug abuse, parental influence, peer influence, anger and self-esteem and cultic behaviour among undergraduates in South-West Nigeria. However, gender, age and self-concept were not significantly correlated with cultic behaviour of undergraduates in South-West Nigeria. Recommendations were made that all stakeholders should be watchful and make concerted efforts to nip the manifestation of the behaviour on the bud to curb the menace of this behaviour in the tertiary institutions.